Conhecimento docente em salas de aula com alunos com transtorno de déficit de atenção e hiperatividade (TDAH) em escolas públicas do município de Paranaguá-PR - Côas, Danielly Berneck (2016)
ADHD is a neurobiological disorder that can begin in childhood and persist during adulthood, compromising the development of the subject in different areas of life, manifesting behaviors of inattention, impulsivity and hyperactivity. This subject is interdisciplinary, but in this research its focus turns to the educational area. Attention deficit hyperactivity disorder is commonly confused by the teacher and the family and their carriers labeled as lazy and without limits, according to Rodhe (1999), Mattos (2003), Benzick (1999), Barkey (2002) and others. This research sought to problematize teachers' knowledge in their professional practice with students with ADHD, enrolled in public (state and municipal) schools in the city of Paranaguá, State of Paraná, Brazil. The specific objectives were contextualized the results of studies that defined and characterized ADHD, the academic production developed in the Postgraduate Programs in masters and doctorates, made available in the Portal of CAPES, between 2011-2012, being analyzed the knowledge That the teachers have about ADHD and the difficulties faced in the care of the student with ADHD, the history of ADHD was investigated, medicalization and non-medicalization to the bearer, the behavior of this student in the school environment before medicalization (not medicalization). Methodologically, the study was characterized by a qualitative exploratory bibliographical review, with a reduced universe of twenty teachers working with students with ADHD, in primary school classes, from public schools in Paranaguá, State of Paraná, Brazil. In the data collection, a semi-structured questionnaire was used as a guide in the collection and subsequent analysis of the participants' answers. The results of the research showed that the teachers presented still incipient knowledge about ADHD, the disciplines that were part of the teacher training did not subsidize to the satisfaction of their pedagogical practices and, for lack of better knowledge about ADHD, they label this student, giving relevance to the field Biological and consequent medicalization. The results of the research led to the conclusion that there are inconsistencies in public policies of social inclusion to students with ADHD. In the thesis, it is concluded that the difficulties in the teaching pedagogical practice in the action with the student with ADHD usually are related to the deficient teacher knowledge, since the university training courses. However, in view of the high number and the number of students with ADHD, it seems that the teachers did not understand or did not have the necessary knowledge of the teachers about the disability, justifying difficulties in developing methodologies that could help in the teaching- Learning.